2016
DOI: 10.3390/foods5030065
|View full text |Cite
|
Sign up to set email alerts
|

Sourdough-Based Biotechnologies for the Production of Gluten-Free Foods

Abstract: Sourdough fermentation, a traditional biotechnology for making leavened baked goods, was almost completely replaced by the use of baker’s yeast and chemical leavening agents in the last century. Recently, it has been rediscovered by the scientific community, consumers, and producers, thanks to several effects on organoleptic, technological, nutritional, and functional features of cereal-based products. Acidification, proteolysis, and activation of endogenous enzymes cause several changes during sourdough ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 86 publications
0
40
0
Order By: Relevance
“…Besides the application of raw materials, the fermentation of flours with lactic acid bacteria (sourdough) is of expanding interest to potentially produce cerealbased foods with slow starch digestibility, mainly due to the formation of organic acids (lactic, acetic and propionic acids), which can lower the rate of starch digestion (Poutanen et al, 2009;Nionelli & Rizzello, 2016). Chemical changes taking place during sourdough have been also postulated to reduce the degree of starch gelatinisation, which would partly explain the lower starch digestibility values of sourdough fermented cereal-based foods (Poutanen et al, 2009).…”
Section: Comparable Results Have Been Reported Inmentioning
confidence: 99%
“…Besides the application of raw materials, the fermentation of flours with lactic acid bacteria (sourdough) is of expanding interest to potentially produce cerealbased foods with slow starch digestibility, mainly due to the formation of organic acids (lactic, acetic and propionic acids), which can lower the rate of starch digestion (Poutanen et al, 2009;Nionelli & Rizzello, 2016). Chemical changes taking place during sourdough have been also postulated to reduce the degree of starch gelatinisation, which would partly explain the lower starch digestibility values of sourdough fermented cereal-based foods (Poutanen et al, 2009).…”
Section: Comparable Results Have Been Reported Inmentioning
confidence: 99%
“…More than 70 species of LAB and 25 species of yeast have been identified in wheat sourdoughs (Moroni et al ; Nionelli and Rizzello ). Minervini et al (, ) found that the two most dominant yeast species in sourdough were S. cerevisiae and K. humilis .…”
Section: Discussionmentioning
confidence: 99%
“…The acidification process, affected by the application of lactic acid bacteria starter or sourdough, is mainly used to improve quality, taste and flavor of wheat breads (Brümmer and Lorenz, 1991 ; Katina et al, 2006a ; Arendt et al, 2007 ) and to delay staling (Katina et al, 2006b ; Plessas et al, 2007 ). Depending on the level of lactic acidification, sourdough fermentation influences bread extensibility, softness, volume and activity of endogenous enzymes (Nionelli and Rizzello, 2016 ). However, a higher acidity could negatively affect bread quality since it can cause off-flavor and reduce loaf volume as well as diminish crumb softness suitable for optimal wheat bread preparation (Kaditzky et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%